2012
DOI: 10.1186/1749-8090-7-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting restoration of kidney function during CRRT-free intervals

Abstract: BackgroundRenal failure is common in critically ill patients and frequently requires continuous renal replacement therapy (CRRT). CRRT is discontinued at regular intervals for routine changes of the disposable equipment or for replacing clogged filter membrane assemblies. The present study was conducted to determine if the necessity to continue CRRT could be predicted during the CRRT-free period.Materials and methodsIn the period from 2003 to 2006, 605 patients were treated with CRRT in our ICU. A total of 222… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 25 publications
2
49
1
1
Order By: Relevance
“…In particular, some studies have focused on the role of NT-proBNP in the weaning from mechanical ventilation (Determann et al 2013;Zhang et al 2014). In contrast to efforts in the field of mechanical ventilation, few studies have been conducted regarding the CRRT weaning (Uchino et al 2009;Heise et al 2012). A previous observational study has found that both the urine output and serum creatinine level at the time of CRRT discontinuation were associated with a low risk of repeat CRRT (Uchino et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, some studies have focused on the role of NT-proBNP in the weaning from mechanical ventilation (Determann et al 2013;Zhang et al 2014). In contrast to efforts in the field of mechanical ventilation, few studies have been conducted regarding the CRRT weaning (Uchino et al 2009;Heise et al 2012). A previous observational study has found that both the urine output and serum creatinine level at the time of CRRT discontinuation were associated with a low risk of repeat CRRT (Uchino et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A previous observational study has found that both the urine output and serum creatinine level at the time of CRRT discontinuation were associated with a low risk of repeat CRRT (Uchino et al 2009). Another observational study has revealed that previous CRRT cycles, the Sequential Organ Failure Assessment score, and urine output after cessation of CRRT affected the outcome of CRRT-free interval (Heise et al 2012). These studies focused on the factors observed during CRRT or at the end of CRRT, not at the initiation of CRRT.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, other studies have previously assessed factors related to successful CRRT discontinuation, but they did not include serum NGAL [11,17,[24][25][26][27][28]. Five studies [11,17,[24][25][26] found that urine output at the time of cessation of CRRT was important for predicting successful CRRT discontinuation.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Five studies [11,17,[24][25][26] found that urine output at the time of cessation of CRRT was important for predicting successful CRRT discontinuation. Uchino et al [11] reported that urine output (OR 1.078/100 mL/ day) and creatinine level (OR 0.996 μmol/L) were significant predictors of successful CRRT discontinuation, and the AUROC curve values for urine output without diuretics and creatinine were 0.808 and 0.635, respectively.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation